Optimisation of Planting Ratio for Hybrid Seed Production in Sponge Gourd - MALLANNA MALAGATTI; VINOD KUMAR PANDITA; SUDIPTA BASU; MOHAMMADATHAR; ANILABHA DASMUNSHI (Seed Research, 2026)
The success of hybrids depends on the availability of quality seeds, which calls for standardization of hybrid seed production technology. ICAR-Indian Agricultural Research Institute, New Delhi released a promising sponge gourd hybrid Pusa Shreshta for commercial cultivation. The present study was carried out the planting ratio to optimize the seed production of this hybrid. The parental lines; DSG-43 (female parent) and DSG-31 (male parent) were sown in planting ratios of 3:1(F:M), 4:1(F:M), and 5:1(F:M) in isolation at IARI-Regional station, Karnal in Kharif 2020 and Spring-Summer 2021. The results showed that the planting ratios had no significant effect on vegetative growth and the flowering behaviour of the parental lines (node number and days to induction of first male and female flower appearance in the vine). However, significant differences were observed for fruit yield, seed yield and quality traits among the planting ratios. In Kharif season, the crop had better vegetative growth, flowering, fruit and seed yield than in the spring-summer season but the seed quality was better in the produce of the latter. Among the planting ratios, 3:1 recorded highest number of fruits/vine, fruit and seed yield/plot and seed quality. The study concluded that a planting ratio of 3:1(female: male) was optimum for hybrid seed production of sponge gourd hybrid Pusa Shreshta in Kharif season under North Indian conditions.